HMGB2 Deficiency Mitigates Abdominal Aortic Aneurysm by Suppressing Ang-II-Caused Ferroptosis and Inflammation via NF-κβ Pathway - Hao Wu; Legao Chen; Kaiping Lu; Yi Liu; Weiqin Lu; Jinsong Jiang; Chao Weng (Hindawi Limited, 2023)
Background. Ferroptosis is a new form of cell death, which is closely related to the occurrence of many diseases. Our work focused on the mechanism by which HMGB2 regulate ferroptosis and inflammation in abdominal aortic aneurysm (AAA). Methods. Reverse transcription-quantitative polymerase chain reaction and western blot were utilized to assess HMGB2 levels. CCK-8 and flow cytometry assays were utilized to measure cell viability and apoptosis. We detected reactive oxygen species generation, Fe2+ level, and ferroptosis-related protein levels in Ang-II-treated VSMCs, which were typical characteristics of ferroptosis. Finally, the mice model of AAA was established to verify the function of HMGB2 in vivo. Results. Increased HMGB2 level was observed in Ang-II-treated VSMCs and Ang-II-induced mice model. HMGB2 depletion accelerated viability and impeded apoptosis in Ang-II-irritatived VSMCs. Moreover, HMGB2 deficiency neutralized the increase of ROS in VSMCs caused by Ang-II. HMGB2 silencing considerably weakened Ang-II-caused VSMC ferroptosis, as revealed by the decrease of Fe2+ level and ACSL4 and COX2 levels and the increase in GPX4 and FTH1 levels. Furthermore, the mitigation effects of shHMGB2 on Ang-II-induced VSMC damage could be counteracted by erastin, a ferroptosis agonist. Mechanically, HMGB2 depletion inactivated the NF-κβ signaling in Ang-II-treated VSMCs. Conclusions. Our work demonstrated that inhibition of HMGB2-regulated ferroptosis and inflammation to protect against AAA via NF-κβ signaling, suggesting that HMGB2 may be a potent therapeutic agent for AAA.